HIV-1 drug resistance and associated risk factors in patients with antiretroviral therapy failure in Chongqing, China, 2019–2023 - Huizheng Zhang; Ping Wu; Wei Ye (PLoS ONE, 2026)
Background The emergence of drug resistance poses a major challenge to the long-term efficacy of antiretroviral therapy (ART) in managing HIV-1 infection. A comprehensive understanding of the prevalence and determinants of HIV-1 drug resistance mutations (DRMs) among patients with treatment failure in Chongqing, China, remains limited. Objectives This study sought to characterize the prevalence of HIV-1 DRMs and to identify factors associated with drug resistance in patients experiencing ART failure in Chongqing between 2019 and 2023. Methods We conducted a retrospective analysis of individuals living with HIV/AIDS who had received ART for at least six months and exhibited virologic failure(VF) (viral load(VL) > 1000 copies/mL). Genotypic resistance testing was performed on plasma samples. Associations between potential risk factors and the presence of DRMs were evaluated using univariate and multivariate logistic regression models. Results Of the 1,522 patients with ART failure included in the study, amplifiable partial pol and integrase (INT) gene sequences were obtained from 1,426 and 653 specimens, respectively. DRMs were identified in 66.55% (949/1,426) of the patients. The predominant HIV-1 subtype was CRF07_BC (50.14%). Class-specific DRM prevalence was highest for non-nucleoside reverse transcriptase inhibitors (NNRTIs) at 61.15%, followed by nucleoside reverse transcriptase inhibitors (NRTIs) at 44.60%, integrase strand transfer inhibitors (INSTIs) at 6.13%, and protease inhibitors (PIs) at 5.39%. The most commonly observed mutations were M184V/I (38.00%) for NRTIs, K103N/S/H (24.96%) for NNRTIs, and M46I (1.54%) for PIs. Multivariate analysis confirmed that lower baseline CD4 + T-cell counts and initiation of treatment with an NNRTI-based regimen were independently associated with the development of DRMs. Conclusions Our study reveals a high prevalence of HIV-1 drug resistance among patients with treatment failure in Chongqing, with low baseline CD4 + T-cell counts and NNRTI-based initial regimens identified as key risk factors. These findings underscore the urgency of optimizing first-line therapy by prioritizing dolutegravir (DTG)-based regimens, with protease inhibitor (PI)-based regimens as a practical alternative. Furthermore, we recommend implementing timely genotypic resistance testing, ideally within 4 weeks upon confirmed virologic failure, to guide effective regimen switching and curb the spread of drug resistance.